The extraordinary educational value of sport - Coco, Daniele (Formazione & insegnamento, 2014)
In our society, gratification, achievement and well-being as sport values are held in high regard only in theory, unfortunately. Indeed, sport values are still defined by generic trends which aren’t punchy enough on experience. Sport values and disvalues will be identified through a pedagogical point of view, and prompts of search and method to apply to concrete situations will be provided. Education to values through sport must be an answer to human needs of growth, of relationship with other people and reality, which can be good or rough, but true indeed.